THE MEDIATING ROLE OF CAREER ADAPTABILITY AND PERSON-JOB FIT ON THE RELATIONSHIP BETWEEN PROACTIVE PERSONALITY AND CAREER SATISFACTION OF COMPANY X FRONTLINE WORKERS IN RIGHTSIZING SITUATIONS - Vellienda, Churnia Dwi; Suhariadi, Fendy; Fajrianthi, Fajrianthi (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to explore career satisfaction as influenced by proactive personality mediated by career adaptability and person-job fit in rightsizing situations for frontline employees of PT. X. This research uses a quantitative research approach. Data analysis used a structural equation modelling-partial least squares (SEM-PLS) approach supported by the Smart-PLS 3.0 computer software programme. Online questionnaires were distributed to 106 respondents. In this study, the respondents were frontline employees who worked at PT X. Proactive personality has no effect on career satisfaction, but has an influence on person-job fit and career adaptability. Career adaptability affects career satisfaction and acts as a mediator in the relationship between proactive personality and career satisfaction. Meanwhile, person-job fit has no effect on career satisfaction and cannot act as a mediator in the relationship between proactive personality and career satisfaction. This research focuses on career satisfaction for frontlines in rightsizing situations. Where this situation provides a limit on the length of work for frontline employees, namely for five years of work. Rightsizing is felt to have an impact on employees during their working period. Therefore, it is necessary to conduct more in-depth research on career satisfaction for employees who get rightsizing policies.